Potencial dos fungos amazônicos Pycnoporus sanguineus E Trametes elegans para biopolpação - Araújo, Solange Pires de (2009)
The Brazilian sector of cellulose pulp and paper has been contributing in an expressive way to the social and economic development of the country as an activity with great growth perspectives; however the increase in demand for cellulose pulp brings about several environmental problems. Alternatives are needed in this sector, improving its economical and environmental sustainability. The biopulping process is enabled by the use of white-rot fungi which act as agents at a previous treatment of wood, these organisms are able to degrade the lignin in a selective way and that enables the process of pulping. Several studies show the capacity of these organisms to degrade the lignin in a selective way, reduce energy consumption and even improve the pulp conditions; however, its industrial use is limited by the make it difficult to inoculate in a large scale and by the presence of contaminators which affect the results of the experiments. Considering the potential of the Amazonian fungi, the present research aimed to assess the potential of the Amazonian fungi Pycnoporus sanguinues and Trametes elegans in the biopulping use with the Simaruba amara Aubl species. Thus, three experiments were carried out, the experiment with S. amara Aubl was characterized as a control for physical- mechanical tests when compared to P. sanguineus and T. elegans. Splinters of wood from S. amara-Aub received inoculations of Pycnoporus sanguineus and Trametes elegans which remained incubated for a period of 60 days, after this period, the splinters of wood were submitted to asepsis in order to remove the mycelium, after removing a small sample for chemical analysis of the three experiments. The baking system used was the Baking Soda (NaOH) with active alkali of 28% for S. amara- Aubl (control) and 18% for P. sanguineus and T. elegans. After that, baking leaves of paper were manufactured and physical-mechanical tests were carried out. In conclusion, P. sanguineus demonstrated to be competitive to degrade the splinters and superior to contaminators when compared to T. elegans. Its enzymatic action was more efficient to extract the lignin. The Amazonian fungus P. sanguineus concluded the study when it was necessary to reduce the alkali percentage for the bakings of the referred fungi. It stood out during physical-mechanical tests when compared to T. elegans and S. amara-Aubl. Thus, the results show the P. sanguíneus Amazonian fungus` potential when compared to T. elegans for biopulping use.